Compostos organoestânicos com ação farmacológica - Flaviana Tavares Vieira (2008)
This work regards the mechanistic investigation of the biological activity of diorganotin complexes of aminobenzoic acid towards C. albicans cells (i); as well as the synthesis, characterization and biological activity of organotin derived of cholic acid (ii), 2,2-2,5-hiophenodiyl-bis(metilenenitrile)]-dibenzoic acid (iii) and 2-(3-oxociclohexen-1-enyl)aminobenzoic acid (iv). Chapter 1 provides a brief of the literature concerning thebiological activity of organotin complexes. It is also described the general aspects of the screened microorganisms. Chapter 2 comprises the experimental details of the synthesis and biological procedures. Chapter 3 reports the in vitro anti-fungal activity of the organotin complexes of aminobenzoic acid (Habz), [Me2Sn(2-OC6H4CH=NC6H4CO2)], [Me2SnO2C(abz)2]2Sn2O2Me4 and [Bu2Sn(abz)2], screened against Candida albicans. The effect of the compounds on the cellular activity of the yeast has been investigated. No change in DNA integrity or in the mitochondria function has been observed. However, all the tin compounds were found to reduce the ergosterol biosynthesis. The compounds have inhibitory concentrations (IC50) in the 7.5 20.0 µg/mL. Scanning electron microscopy and transmission electron microscopy suggest that the organotin complexes act on cell membrane, in view of the cytoplasm leaking and cellular deformation. The data indicate amechanism of action similar to that of polyene drugs, normally used in Candida infections. The triorganotin complexes of aminobenzoic acid were tested towards ten micro-organisms showing promising biological activity in the inhibition of Gram-positive and Gramnegative bacteria. Chapter 4 describes the synthesis and characterization of six organotincomplexes of cholic acid (Hcho), [R3Sn(cho)] and [R2Sn(cho)2], R = Me, Bu and Ph. They have been screened against Artemia salina, displaying the following order of bio-toxicity (mg/mL): [Bu3Sn(cho)] > [Bu2Sn(cho)2] > [Ph3Sn(cho)] > [Ph2Sn(cho)2] > [Me3Sn(cho)] > [Me2Sn(cho)2]. [Bu3Sn(cho)] presented highly ative against the nematode Stongyloidesvenezuelensis, in the growing phase L3. Best results in phase L1 were achieved by complex [Ph2Sn(cho)2]. The antifungal activity of the ligands and the all organotin compounds was tested in Candida albicans, Cryptoccocus neoformans and Cladosporium sphaerospermum. The compounds with the group Me2, Me3 and Bu2 no have activity.[Ph3Sn(cho)] presented high activity antifungal against C. neoformans, in lower dose than that of the ketoconazole, used clinically. All the organotin compounds of cholic acid presented lower cytotoxic activity in human kidney cells (HEK 293) than the ketoconazole. IV Chapter 5 deals with the preparation of the new Schiff base, 2,2-[2,5-tiophenodiyl-bis-(methilenenitrile)]-dibenzoic acid, (H2L), from the reaction of aminobenzoic acid with 2,5-thiophenodicarboxaldehide. The product was employed in the preparation of three diorganotin complexes: [Me2Sn(L)], [Bu2Sn(L)] e [Ph2Sn(L)]. They have been screened for antifungical and antileishmanial activity. The diphenyl derivative has shownantifungical activity against C. albicans and C. neoformans, this activity was lower than ketoconazole. The antileishmanial of the dimethyltin complex was similar to that of the antimoniate of meglumine, however after nine days of culture this complex displayed better activity. Chapter 6 also reports the synthesis of 2-(3-oxociclohex-1-enil)aminobenzoic acid, used as ligand in synthesis of new six organotin complexes. The structure of ligand and the dibuthyl and trimethyl derivatives have been determined to Xray. The antifungal activity showed to [Ph2Sn(boz)O]2 and [Ph3Sn(boz)] against C. neoformans was better than ketoconazole. [Bu2Sn(boz)O]2 not displayed activity towardsTrypanossoma cruzi.